2020
DOI: 10.5603/arm.a2020.0141
|View full text |Cite
|
Sign up to set email alerts
|

Pneumomediastinum and Subcutaneous Emphysema after Noninvasive Ventilation in a COVID-19 Patient

Abstract: An 80-year-old man was admitted because of persistent fever and dyspnea [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…That may indicate that patients after COVID‐19 show increased lung frailty and therefore require careful observation to prevent respiratory deterioration 7 . Some studies show that even patients without invasive ventilation can develop pneumomediastinum and subcutaneous emphysema in the course of COVID‐19 pneumonia 8,9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That may indicate that patients after COVID‐19 show increased lung frailty and therefore require careful observation to prevent respiratory deterioration 7 . Some studies show that even patients without invasive ventilation can develop pneumomediastinum and subcutaneous emphysema in the course of COVID‐19 pneumonia 8,9 …”
Section: Discussionmentioning
confidence: 99%
“…7 Some studies show that even patients without invasive ventilation can develop pneumomediastinum and subcutaneous emphysema in the course of COVID‐19 pneumonia. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vazzana et al reported a case of an 80-year-old patient with severe pneumonia, who required assisted respiration with noninvasive mechanical ventilation. 57 Gorospe et al described a series of 4 cases of patients, with no history of pulmonary illnesses, hospitalised in clinics in Madrid, who were diagnosed with spontaneous pneumomediastinum. 58 Causes of pneumomediastinum are sought in the so-called Makclin effect, that is a sudden increase of pressure in the distal respiratory tract, which results in alveolar ruptures and secondary gas effusion into the pulmonary parenchyma, from which air can eventually reach the mediastinum.…”
Section: Pneumothoraxmentioning
confidence: 99%
“…This leads to air leakage into extra-alveolar tissue, which leads to pneumomediastinum, subcutaneous emphysema, pneumothorax, and pneumoperitoneum [1,2]. During the COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), clinicians encountered many patients who developed barotrauma of varying types and severity during invasive/non-invasive ventilation, and even during spontaneous breathing in some cases [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%